Influence of Work-Family-Conflict and Gender on Parenting Styles among Working Parents in Makurdi Metropolis - Mase, Judith Ayangeawam; Tyokyaa, Tertindi Lordsent (European Scientific Journal, ESJ, 2016)
Parenting styles provide the basis for many developmental outcomes during childhood and beyond. Proper parenting is required for the children to properly adjust in their adult life, as poor parenting has been considered a risk factor for problem behaviour in childhood and later adulthood. This study therefore, examines the influence of work-family conflict on parenting styles among working parents in Makurdi metropolis. A cross-sectional survey was adopted in carrying out the study. A total of 236 working parents involving 108(45.8%) male and 128(54.2%) female parents within the age range of 23-54 years, mean age of 31.84, (SD=8.96) were sampled from a population of working parents in Makurdi metropolis. The Parental Care Scale (Baunmnd, 1991) and Work-Family Conflict Scale (Netemeyer, et al., 1996) were used for the purpose of data collection. Simple linear regression analysis and MANOVA were used in testing the hypotheses. Results revealed a significant influence of work-family conflict on parenting styles among the working parents. A significant difference was also found between male and female working parents on parenting styles. It was concluded that work-family conflict is a significant determinant of parenting styles and that differences in parenting styles also exist between male and female parents. Implications for working parents were discussed and recommendations were also made.